Influence of TaC Powder Additive on electrical discharge machining of stainless Steel - Mohd Zain, Zakaria; Mohammed, Baba Ndaliman; Khan, Ahsan Ali; Mohammad , Yeakub Ali (2011)
Surfaces machined by electrical discharge machining (EDM) can be improved in terms of hardness and corrosion resistance by addition of powder to the dielectric fluid during EDM. In the present study TaC powder was mixed at three different concentrations with kerosene as dielectric fluid during EDM. The output parameters investigated were material removal rate (MRR), surface roughness (SR) and microhardness. During machining, the discharge current was varied between 2.5 and 6.5A, while powder concentration ranges between 5 and 15 g/l. Results indicate that the surface roughness were found to be lowest at 2.5A under long machining periods of various concentrations of the powder. MRR was found to be the highest with the current of 6.5A and powder concentration of 15g/l. Microhardness decreases with increasing current at TaC powder concentration of 15g/l.